Galileu Galilei: Un Occhiale Cavato Dalle Più Recondite Speculazioni Di Prospettiva. - Silva, Jessika Curtinaz Da [UNIFESP] (2018)
The Dissertation Presented Here Has As Its Theme The Approach Between Science And Art Made By Galileo Galilei When Perfecting The Eyeglass, Transforming It Into The Telescope. In The Italian Renaissance, Science And Art Were Speculative And Productive Knowledge, Respectively, And Essentially Diverse. The Union Of These Forms Of Knowledge Was Not Conceivable. Those Who Possessed Speculative Knowledge Did Not Apply Them To Make Objects, And Those Who Possessed Productive Knowledge Did Not Have The Necessary Knowledge To Make And Explain Their Productions. Galileo Galilei, Who Had The Knowledge Of Sciences And Interest In Mechanical Arts, Developed The Eyeglass Possibly Using Mathematical Knowledge, And Created The Telescope. It Was Presented By Galileo In The Sidereus Nuncius, Along With The Results Of The Observations Made By This Instrument.